2020
DOI: 10.1002/chem.202004370
|View full text |Cite
|
Sign up to set email alerts
|

A Promising Approach for Controlling the Second Coordination Sphere of Biomimetic Metal Complexes: Encapsulation in a Dynamic Hydrogen‐Bonded Capsule

Abstract: The design of biomimetic models of metalloenzymes needs to take into account many factorsa nd is therefore ac hallenging task. We propose in this work an original strategy to control the second coordinations phere of a metal centre and its distal environment. Ab iomimetic complex, reproducing the first coordination sphere, is encapsulated in as elf-assembled hydrogen-bondedc apsule. The cationic complex is co-encapsulated with its counter-anion or with solventm olecules. The capsule is dynamic, allowing a fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…In enzymes, substrate binding and positioning is an essential feature to guide a reaction to high selectivity. Although most biomimetic studies have focused on the first-coordination sphere of the oxidant as compared to enzymatic systems, over the years a number of studies have been reported on how the substrate approach can affect reactivity patterns. , In particular, in biomimetic chemistry surrounding an oxidant with bulky groups, placing the short-lived intermediate in a cavity is useful for trapping and characterizing these species. This has been proved particularly useful for CO 2 reduction reactions on metal-porphyrin systems where the encapsulated substrate was tightly bound. …”
Section: Biomimetic Studies On Second-coordination Sphere and Seconda...mentioning
confidence: 99%
“…In enzymes, substrate binding and positioning is an essential feature to guide a reaction to high selectivity. Although most biomimetic studies have focused on the first-coordination sphere of the oxidant as compared to enzymatic systems, over the years a number of studies have been reported on how the substrate approach can affect reactivity patterns. , In particular, in biomimetic chemistry surrounding an oxidant with bulky groups, placing the short-lived intermediate in a cavity is useful for trapping and characterizing these species. This has been proved particularly useful for CO 2 reduction reactions on metal-porphyrin systems where the encapsulated substrate was tightly bound. …”
Section: Biomimetic Studies On Second-coordination Sphere and Seconda...mentioning
confidence: 99%
“…It is important to note that the same reactions performed in the absence of resorcinarene, and thus of a capsular entity, led to poor enantioselectivity [10] . Although encapsulation of cationic metal complexes such as cobalt, [11] copper, [12] gold, [13] iridium, [14] ruthenium [15] or zinc [12] have been reported, only few of the corresponding capsular systems were employed in catalysis. Among these are N ‐heterocyclic carbene gold complexes, which were used in competitive hydration of alkynes, [13c] as well as ruthenium complexes suitable for ring closing metathesis [15b] .…”
Section: Introductionmentioning
confidence: 99%
“…These UV-vis data are consistent with the formation of the azido complex Cu II (Hm-TriA-TPA)(N 3 )(OTf ). 2,7,11 In TPAcomplexes bearing intramolecular H-bonding donors, the potential presence of stabilizing interactions with the azido moiety has been associated with a blue-shift of the LMCT band, as well as a blue-shift of the ν(N-N) stretching frequency. 2,17 The value of the LMCT band observed in the case of Hm-TriA-TPA was therefore compared with that of its To further support the stabilization offered by Hm-TriA-TPA, the two azido complexes have been isolated (see the ESI †) and their antisymmetric N 3 − IR stretch was compared.…”
mentioning
confidence: 99%
“…8 In particular, the archetypal TPA ligand has been equipped with well-defined cavities by means of its covalent substitution, 9,10 or host–guest encapsulation into a H-bonded capsule. 11 In this context, TPA -based hemicryptophanes are organic cages built from a bowl-shaped cyclotriveratrylene (CTV) cap, connected to the tripodal ligand via three linkers. We have recently demonstrated that TPA -hemicryptophanes with methylene or phenyl linkers could, respectively, control the helical arrangement of the ligand 12 and lead to enhanced oxidation catalysts.…”
mentioning
confidence: 99%
See 1 more Smart Citation